2013
DOI: 10.1042/cs20120635
|View full text |Cite
|
Sign up to set email alerts
|

Acute regulation of pancreatic islet microcirculation and glycaemia by telmisartan and ramipril: discordant effects between normal and Type 2 diabetic rats

Abstract: Diabetic patients are often treated with an ACEi (angiotensin-converting enzyme inhibitor) or angiotensin receptor antagonist against hypertension or albuminuria. These drugs also have a positive impact on glucose tolerance, but the mechanism for this remains elusive. Hypothesizing a positive non-additive effect, we studied whether the angiotensin receptor antagonist telmisartan or the ACEi ramipril acutely influence insulin secretion and glycaemia in vivo in healthy and Type 2 diabetic rats through effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
1
1
Order By: Relevance
“…We speculated that the glucose-lowering effect of telmisartan was delayed and weakened in 11-wk-old mice, possibly owing to the progression of insulin resistance and the deterioration of β-cell function in db/db mice. In addition, our data in vivo were not completely consistent with the previous results of telmisartan in regard to acute regulation of pancreatic islet microcirculation and glycaemia ( Olverling et al, 2013 ). The reasons for this discrepancy might conceivably relate to differences in concentrations of drug administration in experiments, and different impaired β-cell function state caused by species and age of the animal model.…”
Section: Resultscontrasting
confidence: 98%
“…We speculated that the glucose-lowering effect of telmisartan was delayed and weakened in 11-wk-old mice, possibly owing to the progression of insulin resistance and the deterioration of β-cell function in db/db mice. In addition, our data in vivo were not completely consistent with the previous results of telmisartan in regard to acute regulation of pancreatic islet microcirculation and glycaemia ( Olverling et al, 2013 ). The reasons for this discrepancy might conceivably relate to differences in concentrations of drug administration in experiments, and different impaired β-cell function state caused by species and age of the animal model.…”
Section: Resultscontrasting
confidence: 98%
“…In a study reported by Anna Olverling et al . 17 , local pancreatic renin-angiotensin system (RAS) controls pancreatic islet blood flow and insulin secretion and thereby may affect blood glucose level. Furthermore, several pancreatic islet RAS signaling pathways seem to be up-regulated by hypertension 18 , 19 .…”
Section: Discussionmentioning
confidence: 99%